Comparison of distance versus in-person laparoscopy training using a low-cost laparoscopy simulator: a randomized controlled multi-center trial - Geißler, Mark Enrik; Bereuter, Jean-Paul; Geissler, Rona Berit; Bökkerink, Guus Mattheus Johannes; Egen, Luisa; Kowalewski, Karl-Friedrich; Haney, Caelán Max (Surgical endoscopy and other interventional techniques, 2024)
Simulation training programs are essential for novice surgeons to acquire basic experience to master laparoscopic skills. However, current state-of-the-art laparoscopy simulators are still expensive, limiting the accessibility to practical training lessons. Furthermore, training is time intensive and requires extensive spatial capacity, limiting its availability to surgeons. New laparoscopic simulators offer a cost-effective alternative, which can be used to train in a digital environment, allowing flexible, digital and personalized laparoscopic training. This study investigates if training on low-cost simulators in a digital environment is comparable to in-person training formats.
Online veröffentlicht: 13. September 2024
Gesehen am 14.01.2025